Analisis Penjualan dan Pembelian Online Produk Ultramilk Coklat 200ml Di PT.Ultrajaya Milk Melalui Marketplace Shopee - Rosana Nabila Septy; Agung Dwi Nugroho; Tri.Wahjoedi (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
In the continually evolving digital era, the implementation of E-Business has become essential for companies to enhance efficiency and reach a broader market. PT. Ultrajaya Milk, a leading milk producer, has utilized the Shopee marketplace platform to market its Ultramilk Chocolate 200ml product. This article analyzes the online sales and purchase process of the product through Shopee, from setting up the online store and uploading products to promotion and marketing. On the buyer's side, the process includes searching and selecting products, adding them to the shopping cart, making payments, and confirming shipments. Once the order is confirmed, funds are transferred from Shopee to PT. Ultrajaya Milk, ensuring transaction security for both parties. Through the implementation of E-Business, PT. Ultrajaya Milk can reach more consumers with high operational efficiency. This article provides a step-by-step guide complete with images of the sales and purchase processes, highlighting the importance of E-Business in facilitating a convenient and secure shopping experience for customers.